High Folate and Vitamin Low B12 Status: Potential Interactions with Cognitive Function Among U.S. Older Adults, NHANES 2011–2014. (29th May 2020) - Bailey, Regan; Jun, Shinyoung; Murphy, Lisa; Green, Ralph; Miller, Josh
Abstract: Objectives: Potential safety concerns may exist with high folate/folic acid exposures combined with low vitamin B12 (B12) status relative to cognitive function; therefore, we investigated this relationship, leveraging cognitive test performance with folate and B12 biomarker data among a nationally-representative survey of U.S. older adults. Methods: We analyzed data from 2420 older adults (≥60 y) from the 2011–2014 NHANES. High folate status was defined as unmetabolized serum folic acid (UMFA) > 1 nmol/L or serum folate > 74.1 nmol/L. Low B12 status was defined using age-specific cut-points for serum B12 [≤429 pmol/L (in 60–69 y) and ≤370 pmol/L (in ≥70 y)] or using a combination of traditional cut-points [elevated methylmalonic acid (>271 nmol/L) and deficient serum B12 (< 150 pmol/L)]. Multivariable logistic regression models estimated odds ratios (OR) of scoring low on one of four cognitive tests: Digit Symbol Substitution Test (DSST), Consortium to Establish a Registry for Alzheimer's Disease [CERAD; Word Learning (WL) and Delayed Recall (DR)], and Animal Fluency Test (AF). Results: Among older adults with low B12 status, high UMFA was associated with a higher OR of having a low score on the DSST (<34, OR 2.16; 95% CI 1.05–4.47) and high serum folate was associated with a higher OR of having a low score on the AF (<14, OR 1.93; 95% CI 1.08–3.45), only when using traditional cut-points for B12. Among those with normal B12 status, having a high UMFA was protective on the CERAD-DR, regardless of B12 status being defined using age-specific or traditional cut-points. Compared to those with normal B12 (using traditional cut-points) and high UMFA, those with low B12 and high UMFA had a higher risk of scoring low on the DSST (<40, OR 2.22; 95% CI 1.31–3.75) and AF (<14, OR 1.97; 95% CI 1.30–2.97), those with low B12 and lower UMFA had a higher risk of scoring low on the DSST (<40, OR 1.69; 95% CI 1.16–2.47), and those with normal B12 and lower UMFA had a higher risk of scoring low on the CERAD-DR (<17, OR 1.38; 95% CI 1.02–1.85); similar patterns were found with serum folate. Conclusions: In older adults, high folate was associated with better cognitive performance when vitamin B12 status is normal, whereas high folate was associated with poorer cognitive performance when vitamin B12 status is low. Funding Sources: N/A.